Analysis of firm size, leverage, corporate governance on earnings management practices (Indonesian evidence) - Indra Satya Prasavita Amertha; I Gusti Ketut Agung Ulupui; I Gusti Ayu Made Asri Dwija Putri (Universitas Hayam Wuruk Perbanas, 2014)
The inconsistency of the results in previous studies related to the relationship of firm size and leverage on earnings management practices is still interesting. In contrast to the previous studies, this study is not merely to determine the effect of firm size, leverage,and corporate governance on earnings management practices partially but also to include the variable corporate governance (CG) is also thought to be able to moderatethe effect of firm size and leverage variables on earnings management practices.Discretionary accruals as proxy for earnings management and are also measured using Performance-Matched Discretionary Accruals Model. Using Moderated Regression Analysis (MRA) and Residual Test, the result shows that firm size and corporate governance have a significant effect on earnings management, whereas the leverage was not found to have a significant effect. In addition, the results of this study indicate that corporate governance is able to moderate the relationship firm size and leverage on earnings management practices.